Tema, Fungsi, dan Nilai dalam Cerita Rakyat “Asal Usul Desa Selakambang” - Henry Trias Puguh Jatmiko; Fendi Setiawan (Jurnal Guru Indonesia, 2022)
AbstractThis research is a qualitative descriptive study that aims to describe and explain the themes, functions, and values of the folklore of Selakambang Village. Data and information are collected through informants and documents. Data were collected through observation, interviews, recordings, and document analysis. The research sample was determined by the snowball sampling technique. Data validation is done by data triangulation. The result of this research is the theme of the folklore entitled The Origin of Selakambang Village is Patriotism and Leadership. While the function of folklore consists of four things, namely the aesthetic function, pragmatic function, ethical function, and historical function. Based on the analysis of the values contained in the folklore of Selakambang Village, it can be concluded that in the folklore there are four values, namely: cultural, religious, moral, and historical. This research has implications for the value of education and moral values in it which are devoted to readers, especially the younger generation so that they can apply them in everyday life. Another implication is the preservation of the folklore of Selakambang village both in writing and orally. AbstrakPenelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk mendeskripsikan dan menjelaskan tema, fungsi serta nilai dari cerita rakyat Desa Selakambang. Data dan informasi dikumpulkan melalui informan dan dokumen. Pengumpulan data dilakukan melalui observasi, wawancara, rekaman, dan analisis dokumen. Sampel penelitian ditentukan dengan teknik snowball sampling. Validasi data dilakukan dengan triangulasi data. Hasil penelitian ini adalah tema cerita rakyat yang berjudul Asal Usul Desa Selakambang adalah Patriotisme dan Kepemimpinan. Sedangkan fungsi cerita rakyat terdiri atas empat hal yaitu fungsi estetis, fungsi pragmatis, fungsi etis dan fungsi historis. Berdasarkan analisis tentang nilai yang terdapat dalam cerita rakyat Desa Selakambang dapat disimpulkan bahwa dalam cerita rakyat ditemukan empat nilai, yaitu: budaya, religius, moral, dan sejarah. Penelitian ini berimplikasi pada nilai pendidikan dan nilai-nilai moral di dalamnya yang dikhususkan untuk pembaca khususnya generasi muda agar dapat menerapkan dalam kehidupan sehari-hari. Implikasi lainnya yaitu lestarinya cerita rakyat desa Selakambang baik secara tertulis maupun lisan.